Marxism as a tool for uncovering hegemonic discourses on nature. Issue 1 (March 2022) - González, Fernando
Since its origins, geography has prioritized the study of nature. However, more recently the discipline has made advancements in studying power as a fundamental element in the social production of space and territory. What can Marxism offer to such investigations? In this brief article, I highlight some of the contributions of Marxist thought that I have found useful for geographic analysis and that stand out from the discipline's other forms of analysis. Firstly, I recover elements from the thinker Antonio Gramsci that I consider important for debates regarding the social production of space and territory as an expression of power relations. Secondly, I retrace some aspects of Marx's concept of nature to examine certain notions that prevail in today's environmental debates. In this way, I look to denaturalize the hegemonic thought with which institutions and dominant classes exercise power in this area.